Method for coating surface of carbon fiber with silicon carbide
Through the steps of dipping, oxidizing and non-melting and carbonizing sintering of liquid polycarbosilane, the problem of uneven silicon carbide coating on the surface of carbon fiber is solved, achieving efficient anti-ablation protection of carbon fiber, and is suitable for coating long carbon fibers.
Patent Information
- Application Number
- CN202310883526.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art has an uneven problem when silicon carbide is applied to the carbon fiber surface, which leads to the inadequate ablation resistance and the inability to effectively coat on continuous long carbon fibers.
Liquid polycarbosilane is used as the silicon carbide precursor, and the silicon carbide layer is evenly coated and fixed through three steps of dipping, oxidation and infusibility, and carbonization and sintering to ensure that it is closely combined with the carbon fiber matrix.
The uniformity and tight combination of the silicon carbide coating on the surface of the carbon fiber are achieved, which significantly improves the ablation resistance of the fiber and can effectively protect the long carbon fiber and extend its service life.
Smart Images

Figure CN119332501A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-performance carbon fiber preparation, and specifically relates to a method for coating silicon carbide on the surface of carbon fiber. Background Art
[0002] High thermal conductivity carbon fiber has excellent properties such as high strength, high modulus, high thermal conductivity, and low thermal expansion coefficient. It is very suitable for the outer space environment with large temperature difference between day and night. It has been used in various spacecraft, such as structural / functional composite materials for satellite shells, satellite high-power heat sinks, solar cell back panels for space stations, launch vehicle engine nozzles, etc. It is also increasingly widely used in new hypersonic aircraft engines, wing leading edges, rudders, airborne phased array radar launch surfaces, etc. Its excellent performance has now become an indispensable material in occasions that require heat dissipation and precision stability, and has a huge driving effect on the performance improvement of weapons and aerospace equipment.
[0003] High thermal conductivity carbon fiber has a series of excellent properties, but it also has a disadvantage that cannot be ignored, that is, it is easy to be oxidized when it exceeds 400℃. When the aircraft flies at supersonic speed in the atmosphere, the hot end parts of the aircraft, such as the nose cone and the leading edge of the wing, will increase sharply with the increase of Mach number due to the heating of the high-temperature compressed gas between the shock wave and the fuselage and the strong friction between the fuselage surface and the air. When these parts are subjected to the thermal load impact of ultra-high temperature and high-speed airflow of up to 2000-3000℃, the carbon fiber in the composite material can be severely ablated, resulting in surface erosion, which will damage the high lift-to-drag ratio and aerodynamic shape of the aircraft, making it impossible to guarantee the control accuracy in a severe ablation environment.
[0004] In order to solve the above problems, the commonly used method is to add ablation-resistant additives to the composite materials to slow down the occurrence of this phenomenon. However, the preparation process of existing composite materials determines that this method can only play a certain role in slowing down ablation in actual operation and cannot completely solve the problem.
[0005] Patent CN201910452575 discloses a method for coating carbon fiber with silicon carbide, coating the fiber surface with a layer of ablation-resistant material silicon carbide. The specific method is to heat the carbon fiber for pretreatment and then cool it to room temperature; mix silicon carbide powder and silicone rubber at a mass ratio of 5-10:100 to obtain a mixed slurry; fully mix the carbon fiber and the mixed slurry at a mass ratio of 3-5:100; heat the carbon fiber fully impregnated with the slurry to 400-600°C, react for 1-2 hours, and then cool it to room temperature to obtain a carbon fiber with a silicon carbide coating on the surface.
[0006] The above method has the following defects: First, the method described in the patent uses silicon carbide powder mixed with silicone rubber and then mixed with carbon fiber, and the density difference between the three is large (silicon carbide density is 3.22g / cm 3 , dimethyl silicone rubber density 1.1 ~ 1.2g / cm3, carbon fiber density 1.7 ~ 2.2g / cm 3 ), there is a problem of difficulty in mixing.
[0007] Secondly, the silicon carbide coating on the surface of the carbon fiber prepared by this patent is only the physical adhesion formed by the silicon carbide powder through the bonding of silicone rubber, and does not form a chemical bond because no chemical reaction can occur under the conditions of 400-600°C to form silicon carbide compounds.
[0008] The third is to attach Figure 3 It can be seen that the silicon carbide coating prepared by this method is relatively loose. The main reason is that dimethyl rubber is easy to foam at high temperature, which is bound to cause large voids on the surface of carbon fiber, thereby reducing the fiber's anti-ablation ability.
[0009] Fourth, carbon fiber begins to oxidize in an oxidative atmosphere above 400°C, which has a great impact on the mechanical properties of the fiber.
[0010] Fifth, the method described in the patent can only be used for chopped carbon fibers but not for fiber filaments. It can only be used as a filler for related composite materials but not as a reinforcement, and is of no benefit in improving the mechanical properties of composite materials. Summary of the invention
[0011] The purpose of the present invention is to provide a method for coating silicon carbide on the surface of carbon fiber in response to the above-mentioned defects. The method can solve the problem that the silicon carbide coated on the surface of carbon fiber in the prior art is uneven, resulting in the inability to fully exert the anti-ablation performance of silicon carbide. It also solves the current difficulty of not being able to coat silicon carbide (PCS) on continuous long carbon fiber.
[0012] The technical solution of the present invention is:
[0013] A method for coating silicon carbide on the surface of carbon fiber comprises the following steps:
[0014] (1) Dipping: First, polycarbosilane is placed in a dipping tank in a heating furnace under nitrogen protection, and heated to obtain molten polycarbosilane; wherein the nitrogen protection is used to prevent oxidative decomposition of polycarbosilane;
[0015] Then the carbon fiber is pulled into the dipping tank, and the distribution thickness of the molten polycarbosilane on the carbon fiber surface is controlled by adjusting the tension applied to the carbon fiber. The pulling rate is in accordance with the pulling rate range of the existing normal production of carbon fiber. The adjustment of the tension can control the tightness of the fiber. The larger the tension, the tighter the fiber, and the smaller the tension, the looser the fiber. The tension applied to the carbon fiber can be adjusted using the existing tension control instrument in the field.
[0016] The above-mentioned molten polycarbosilane is a liquid with a polycarbosilane content of 100%, with high viscosity and high solution temperature. When the carbon fiber is immersed in the molten polycarbosilane, a layer of liquid polycarbosilane will adhere evenly and continuously to the surface to form a uniform polycarbosilane coating, which is then formed into a silicon carbide coating with uniform thickness through heat treatment.
[0017] The carbon fiber is drawn into the dipping tank to be impregnated with molten polycarbosilane, thereby achieving continuous silicon carbide coating without affecting the strength and continuity of the fiber. Long carbon fibers can be continuously coated with silicon carbide.
[0018] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 170-250°C for 1-3 hours.
[0019] This step is different from the curing process in the prior art in which the solidified layer is formed by evaporating and removing the solvent. Instead, the liquid polycarbosilane surface undergoes an oxidation reaction with oxygen in the range of 170 to 250°C to form a stable coating to prevent the fibers from sticking to each other after coating.
[0020] (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated and carbonized at a constant temperature under a nitrogen atmosphere, so that the oxidized polycarbosilane on the surface of the carbon fiber is carbonized into silicon carbide, thereby obtaining a carbon fiber with a silicon carbide coating on the surface.
[0021] The above coating method mainly goes through three stages, namely the physical process of dipping, and the two chemical reaction processes of oxidation infusibility and carbonization sintering.
[0022] In the dipping stage, according to different product requirements, the carbon fiber can be immersed in molten polycarbosilane (PCS) and the fiber tension can be controlled to coat the carbon fiber surface with a polycarbosilane (PCS) layer of required thickness. It can be seen that the technical solution of the present invention has wide applicability in actual production.
[0023] Then, oxygen is introduced into polycarbosilane (PCS) through an infusible treatment, transforming it from a thermoplastic resin to a network-crosslinked thermosetting resin.
[0024] The oxidation-infusibility reaction is as follows:
[0025] ~Si-H(PCS)+O2 →~Si-O-Si+H 2
[0026] Wherein: ~Si-H represents polycarbosilane (PCS).
[0027] Then, the polycarbosilane crosslinked body is gradually dehydrogenated and deoxidized into silicon carbide through a carbonization reaction, thereby preparing carbon fiber with silicon carbide coating.
[0028] The reaction of carbonization sintering is as follows:
[0029] ~Si-H(PCS)+~Si-H(PCS)→C-Si-C+H 2 .
[0030] In the present invention, the density of polycarbosilane in step (1) of the method for coating silicon carbide on the surface of carbon fiber is 1.05 to 1.15 g / cm 3 ; Molecular weight is 1000-2000; Softening point is 180-240°C. The use of this polycarbosilane can reduce the foaming and weight loss that occur during the thermal cross-linking and curing process of PCS.
[0031] In the present invention, in step (1) of the method for coating the surface of carbon fiber with silicon carbide, the temperature is raised to 200-350° C. If the temperature is higher than 350° C., the polycarbosilane will be thermally decomposed.
[0032] In the present invention, in step (1) of the method for coating the surface of carbon fiber with silicon carbide, the carbon fiber is 1 to 12K continuous bundles, wherein K represents the number of fibers, 1K generally means that a bundle of fibers contains 1000 fibers; and the diameter of the single fiber is 5 to 15 μm.
[0033] In the present invention, the nitrogen flow rate of nitrogen protection in step (1) of the method for coating silicon carbide on the surface of carbon fiber is 1 to 10 m 3 / hr. If the nitrogen flow rate is too high, it will cause fiber disturbance, and if it is too low, it will not play the role of inert gas protection.
[0034] In the present invention, the tension applied to the carbon fiber in step (1) of the method for coating the carbon fiber surface with silicon carbide is 10 to 60 N. The magnitude of the tension plays an important role in ensuring whether the PCS coating is uniform. If the tension is too large, the carbon fiber will break and the continuity of the fiber will be destroyed; if the tension is too small, the PCS coating will be uneven and the coating amount will be too large.
[0035] In the present invention, in step (3) of the method for coating the carbon fiber surface with silicon carbide, the temperature is heated to 900-1500°C, and the constant temperature carbonization time is 10-60 minutes. Within the temperature range, not only is polycarbosilane (PCS) converted into silicon carbide, but the carbonization time is also greatly shortened.
[0036] In the present invention, in step (3) of the method for coating silicon carbide on the surface of carbon fiber, the temperature is heated to 900-1300°C.
[0037] A carbon fiber with a silicon carbide coating on the surface, wherein the silicon carbide coating is prepared by the coating method, and the thickness of the silicon carbide coating is 0.1-0.15 μm.
[0038] In the present invention, the carbon fiber with silicon carbide coating on the surface has a burning rate of less than 4% at 1000°C and a burning rate of less than 10% at 1500°C.
[0039] The beneficial effects of the present invention are as follows: the present invention uses liquid polycarbosilane (PCS) as a silicon carbide precursor, which can be evenly coated on the surface of carbon fiber, and becomes a carbon fiber coating through air infusibility and carbonization sintering, and the silicon carbide coating is tightly combined with the carbon fiber matrix.
[0040] Compared with the prior art that uses strong acid or the like to treat the fiber surface, the present invention directly coats the fiber surface without the need for surface treatment of the fiber, and will not damage the mechanical properties of the carbon fiber.
[0041] The present invention can coat the surface of long fibers with silicon carbide, and the obtained carbon fibers can be used as excellent reinforcements for high-temperature resistant composite materials, thereby improving the thermal ablation resistance of the composite materials.
[0042] In addition, the present invention improves the mechanical properties of carbon fiber because silicon carbide makes up for defects such as cracks on the surface of carbon fiber, thereby improving the mechanical properties of carbon fiber composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a scanning electron microscope (SEM) image of the silicon carbide coating prepared in Example 2.
[0044] Figure 2 This is a scanning electron microscope (SEM) image of the silicon carbide coating prepared in Example 4.
[0045] Figure 3 for Figure 2 A partial enlarged view of .
[0046] Figure 4 This is a scanning electron microscope (SEM) image of the silicon carbide coating prepared in Comparative Example 3.
[0047] Figure 5 This is a scanning electron microscope (SEM) image of the silicon carbide coating prepared in Comparative Example 4.
[0048] Figure 6 for Figure 5 A partial enlarged view of . DETAILED DESCRIPTION
[0049] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings.
[0050] 1. Source of raw materials:
[0051] Polycarbosilane was purchased from Shanghai Buwei Applied Materials Technology Co., Ltd., density: 1.05-1.15 g / cm 3 , molecular weight: 1000~2000, softening point: 180~240℃.
[0052] The carbon fiber is the high thermal conductivity carbon fiber bundle products RCHCF-600 (thermal conductivity 600W / m·K, tensile strength 2800MPa) and RCHCF-800 (thermal conductivity 800W / m·K, tensile strength 3200MPa) produced by Shandong Ruicheng Aerospace Carbon Material Co., Ltd.
[0053] 2. Data measurement method:
[0054] 1. Thermal conductivity is based on GB / T 22588-2008 and is tested using the flash thermal conductivity instrument LFA467.
[0055] 2. The tensile strength was tested according to GB / T3362-2017 using instron 5967. Since comparative examples 3 and 4 were both short fibers, the above standards could not measure their thermal conductivity and tensile strength.
[0056] 2. Test method for ablation resistance of carbon fiber: Weigh a certain amount of fiber (accurate to 0.0001g) with a porcelain boat, and then use a muffle furnace to keep the temperature at 500℃, 1000℃, and 1500℃ for 20 minutes respectively, weigh the remaining mass, and calculate the burning rate by the following formula:
[0057] M=(m 1 -m 2 ) / m 1 ×100%
[0058] Where: M: burning rate;
[0059] m 1 : Original mass of the sample;
[0060] m 2 : Mass of sample after ablation.
[0061] Example 1
[0062] The method for coating silicon carbide on the surface of carbon fiber has the following specific operating steps:
[0063] (1) Dipping: Place polycarbosilane in a 5m 3 / hr flow rate into the dipping tank in the heating furnace of nitrogen, heating to 200°C, and then pulling the carbon fiber (model: RCHCF-600-1K) into the dipping tank, the tension applied to the carbon fiber is 10N;
[0064] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 170°C for 1 hour;
[0065] (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated to 900° C. in a nitrogen atmosphere and carbonized at a constant temperature for 10 min to obtain a carbon fiber having a silicon carbide coating on the surface, wherein the thickness of the silicon carbide coating is 0.15 μm.
[0066] Example 2
[0067] The method for coating silicon carbide on the surface of carbon fiber has the following specific operating steps:
[0068] (1) Dipping: Place polycarbosilane in a 5m 3 / hr flow rate into the dipping tank in the heating furnace of nitrogen, heating to 200°C, and then pulling the carbon fiber (model: RCHCF-600-3K) into the dipping tank, the tension applied to the carbon fiber is 10N;
[0069] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 200°C for 2h;
[0070] (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated to 900° C. in a nitrogen atmosphere and carbonized at a constant temperature for 10 min to obtain a carbon fiber having a silicon carbide coating on the surface, wherein the thickness of the silicon carbide coating is 0.15 μm.
[0071] Example 3
[0072] The method for coating silicon carbide on the surface of carbon fiber has the following specific operating steps:
[0073] (1) Dipping: Place polycarbosilane in a 5m 3 / hr flow rate into the dipping tank in the heating furnace of nitrogen, heating to 200°C, and then pulling the carbon fiber (model: RCHCF-600-6K) into the dipping tank, the tension applied to the carbon fiber is 10N;
[0074] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 200°C for 2h;
[0075] (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated to 1100° C. under a nitrogen atmosphere and carbonized at a constant temperature for 20 min to obtain a carbon fiber having a silicon carbide coating on the surface, wherein the thickness of the silicon carbide coating is 0.15 μm.
[0076] Example 4
[0077] The method for coating silicon carbide on the surface of carbon fiber has the following specific operating steps:
[0078] (1) Dipping: Place polycarbosilane in a 5m 3 / hr flow rate into the dipping tank in the heating furnace of nitrogen, heating to 300°C, and then pulling the carbon fiber (model: RCHCF-800-6K) into the dipping tank, the tension applied to the carbon fiber is 30N;
[0079] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 200°C for 3 hours;
[0080] (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated to 1300° C. under a nitrogen atmosphere and carbonized at a constant temperature for 20 min to obtain a carbon fiber having a silicon carbide coating on the surface, wherein the thickness of the silicon carbide coating is 0.12 μm.
[0081] Example 5
[0082] The method for coating silicon carbide on the surface of carbon fiber has the following specific operating steps:
[0083] (1) Dipping: Place polycarbosilane in a 5m 3 / hr flow rate into the dipping tank in the heating furnace of nitrogen, heating to 300°C, and then pulling the carbon fiber (model: RCHCF-800-12K) into the dipping tank, the tension applied to the carbon fiber is 60N;
[0084] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 230 °C for 1 h;
[0085] (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated to 1300° C. under a nitrogen atmosphere and carbonized at a constant temperature for 10 min to obtain a carbon fiber having a silicon carbide coating on the surface, wherein the thickness of the silicon carbide coating is 0.1 μm.
[0086] Example 6
[0087] The method for coating silicon carbide on the surface of carbon fiber comprises the following steps:
[0088] (1) Dipping: Place polycarbosilane in a 5m3 / hr flow rate into the dipping tank in the heating furnace of nitrogen, heating to 300°C, and then pulling the carbon fiber (model: RCHCF-800-12K) into the dipping tank, the tension applied to the carbon fiber is 60N;
[0089] (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 230 °C for 2 h;
[0090] (3) Carbonization sintering: The carbon fiber in step (2) is introduced into a carbonization furnace, heated to 1500°C by nitrogen, and carbonized at a constant temperature for 10 minutes to obtain a carbon fiber with a silicon carbide coating on the surface, wherein the thickness of the silicon carbide coating is 0.1 μm.
[0091] Comparative Example 1
[0092] The thermal conductivity, tensile strength and ablation rate of high thermal conductivity carbon fiber RCHCF-600-3K were measured.
[0093] Comparative Example 2
[0094] The thermal conductivity, tensile strength and ablation rate of high thermal conductivity carbon fiber RCHCF-800-12K were measured.
[0095] Comparative Example 3
[0096] The technical solution of Example 2 in patent CN110158309 is adopted.
[0097] (1) Pre-treat carbon fibers with a length of 2 mm and a diameter of 7 μm in a muffle furnace at 400 °C for 1 h and then cool to room temperature.
[0098] (2) SiC powder with a particle size of 50 nm and a purity of 99.99 wt% and dimethyl silicone rubber with a viscosity of 7000 MPa·s and a silicone rubber mass ratio of 10:100 were mixed and stirred to obtain a slurry, and mechanically stirred at 300 r / min for 12 h;
[0099] (3) The carbon fiber and SiC slurry were fully mixed and mechanically stirred at 300 r / min for 12 h, wherein the mass ratio of carbon fiber to slurry was 3:100;
[0100] (4) The fully impregnated carbon fiber is placed in a muffle furnace at 500° C. for 1 hour and then cooled to room temperature to obtain a carbon fiber with a silicon carbide coating on the surface.
[0101] Comparative Example 4
[0102] The technical solution of Example 6 in patent CN110158309 is adopted.
[0103] (1) A carbon fiber with a length of 5 mm and a diameter of 10 μm was placed in a muffle furnace, heated at 400 °C for 1 h, and then cooled to room temperature;
[0104] (2) SiC powder with a particle size of 50 nm and a purity of 99.99 wt% and dimethyl silicone rubber with a viscosity of 7000 MPa·s were mixed in a mass ratio of 10:100, and mechanically stirred at a speed of 600 r / min for 12 h to obtain a mixed slurry;
[0105] (3) The carbon fiber and the mixed slurry are mixed in a mass ratio of 5:100, and mechanically stirred at a speed of 600 r / min for 12 hours; (4) The carbon fiber fully impregnated with the slurry is heated to 600°C, reacted for 1 hour, and then cooled to room temperature to obtain a carbon fiber with a silicon carbide coating on the surface.
[0106] The thermal conductivity, tensile strength and ablation rate of the carbon fibers in the embodiments and comparative examples are measured below. The measurement results are shown in Table 1.
[0107] Table 1
[0108]
[0109] It can be seen from Table 1 that the silicon carbide coatings in Examples 1-6 can provide good high-temperature protection for the fibers, and the carbon fibers without the protection of the silicon carbide coatings will burn out quickly at high temperatures.
[0110] pass Figure 1 , Figure 2 and Figure 3 It can be seen that the coatings prepared in the present invention are relatively dense and are evenly distributed around the carbon fiber.
[0111] pass Figure 4 , Figure 5 and Figure 6 It can be seen that the silicon carbide coatings formed in Comparative Examples 3 and 4 are relatively fluffy, or the coating effect is poor (such as Figure 4 As shown), or the coating is uneven and easy to fall off (as shown Figure 5 and Figure 6 This will cause more oxygen to enter, and the silicon carbide coating will not actually provide good protection.
Claims
1. A method for coating silicon carbide on the surface of carbon fiber, characterized in that: The following steps are involved: (1) Dipping: First, polycarbosilane is placed in a dipping tank in a heating furnace under nitrogen protection, and heated to obtain molten polycarbosilane; Then the carbon fiber is pulled into the dipping tank, and the distribution thickness of the molten polycarbosilane on the surface of the carbon fiber is controlled by adjusting the tension applied to the carbon fiber; (2) Oxidation infusibility: The impregnated carbon fiber is introduced into an infusible furnace, air is introduced, and treated at 170-250°C for 1-3 hours; (3) Carbonization sintering: The carbon fiber obtained in step (2) is introduced into a carbonization furnace, heated and carbonized at a constant temperature under a nitrogen atmosphere, so that the oxidized polycarbosilane on the surface of the carbon fiber is carbonized into silicon carbide, thereby obtaining a carbon fiber with a silicon carbide coating on the surface.
2. The method for coating silicon carbide on the surface of carbon fiber according to claim 1, characterized in that: The density of the polycarbosilane in step (1) is 1.05 to 1.15 g / cm 3 ; Molecular weight is 1000-2000; Softening point is 180-240℃.
3. The method for coating silicon carbide on the surface of carbon fiber according to claim 1, characterized in that: In the step (1), the temperature is raised to 200-350°C.
4. The method for coating silicon carbide on the surface of carbon fiber according to claim 1, characterized in that: In the step (1), the carbon fiber is 1-12K continuous bundles, and the diameter of the single fiber is 5-15 μm.
5. The method for coating silicon carbide on the surface of carbon fiber according to claim 1, characterized in that: The nitrogen flow rate of nitrogen protection in step (1) is 1 to 10 m 3 / hr.
6. The method for coating silicon carbide on the surface of carbon fiber according to claim 1, characterized in that: The tension applied to the carbon fiber in step (1) is 10 to 60N.
7. The method for coating silicon carbide on the surface of carbon fiber according to claim 1, characterized in that: In the step (3), the temperature is heated to 900-1500° C., and the constant temperature carbonization time is 10-60 minutes.
8. The method for coating silicon carbide on the surface of carbon fiber according to claim 7, characterized in that: In the step (3), the temperature is heated to 900-1300°C.
9. A carbon fiber having a silicon carbide coating on its surface, characterized in that: The silicon carbide coating is prepared by the coating method as described in claims 1-8, and the thickness of the silicon carbide coating is 0.1-0.15 μm.
10. The carbon fiber having a silicon carbide coating on the surface according to claim 9, characterized in that: The burning rate of the carbon fiber at 1000° C. is less than 4%; and the burning rate at 1500° C. is less than 10%.
Citation Information
Patent Citations
Method for preparing carbon fiber with silicon carbide coating on surface
CN110158309A